Biomechanics of graded running: Part I - Stride parameters, external forces, muscle activations - Vernillo, G.; Martinez, A.; Baggaley, M.; Khassetarash, A.; Giandolini, M.; Horvais, N.; Edwards, W. B.; Millet, G. Y. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Biomechanical alterations with graded running have only been partially quantified, and the potential interactions with running speed remain unclear. We measured spatiotemporal parameters, ground reaction forces, and leg muscle activations (EMG) in nineteen adults (10F/9M) running on an instrumented treadmills at 2.50, 3.33, and 4.17 m·s-1 and 0, ±5°, and ±10°. Step frequency illustrated a significant speed × grade interaction (P < .001) and was highest (+3%) at the steepest grade (+10°) and fastest speed (4.17 m·s-1) when compared to level running (LR) at the same speed. Significant interaction was also observed for ground reaction forces (all P = .047). Peak ground reaction forces in the normal direction increased with running speed during downhill running (DR) only (+9% at -10° and 4.17 m·s-1). Impulse in the normal direction decreased at fastest speed and steepest DR (-9%) and uphill running (UR) (-17%) grades. Average normal loading rate increased and decreased at fastest speed and steepest DR (+52%) and UR (-28%) grades, respectively. Negative parallel impulse increased and decreased at fastest speed and steepest DR (+166%) and UR (-90%), respectively. Positive parallel impulse decreased and increased at fastest speed and steepest DR (-75%) and UR (+111%), respectively. EMG showed comparable u-shaped curves across the grades investigated, although only a change in vastus lateralis and tibilias anterior activity was detectable at the steepest grades and fastest speed. Overall, running grade and speed significantly influences spatiotemporal parameters, ground reaction forces, and muscle activations.